2010
DOI: 10.1159/000319804
|View full text |Cite
|
Sign up to set email alerts
|

Significant Association between <i>IL-17F</i> Promoter Region Polymorphism and Susceptibility to Asthma in a Korean Population

Abstract: Background: Individual differences in susceptibility to asthma would be expected because of common DNA variants of single nucleotide polymorphisms (SNPs) across populations. The pro-inflammatory cytokine IL-17F has homology with the IL-17 motif and induces the expression of other inflammatory cytokines in airway epithelial cells. This study aimed to identify IL-17F gene polymorphisms and to determine a possible association between these polymorphisms and susceptibility to asthma through a case-control study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…These associations are consistent with in vitro findings that IL‐17A can promote neutrophil migration through IL‐8 stimulation by facilitating neutrophil transmigration . Various studies have identified genetic variants of IL‐17A and IL‐17F to be associated with asthma risk but none has dealt with severe asthma . Hence, IL‐17 signalling pathway may be associated with a subset of patients characterized as having ‘neutrophilic’ asthma.…”
Section: Cytokine Signalling Pathwayssupporting
confidence: 85%
“…These associations are consistent with in vitro findings that IL‐17A can promote neutrophil migration through IL‐8 stimulation by facilitating neutrophil transmigration . Various studies have identified genetic variants of IL‐17A and IL‐17F to be associated with asthma risk but none has dealt with severe asthma . Hence, IL‐17 signalling pathway may be associated with a subset of patients characterized as having ‘neutrophilic’ asthma.…”
Section: Cytokine Signalling Pathwayssupporting
confidence: 85%
“…Multiple previous studies have reported an association between IL-17 gene polymorphisms and autoimmune diseases (Jin et al, 2011;Zhang et al, 2013;Maalmi et al, 2014;Shen et al, 2015). Jin et al (2011) reported an association between IL-17 gene polymorphisms and susceptibility to asthma in a Korean population, and suggested that the rs1889570 polymorphism was correlated with the development of asthma.…”
Section: Discussionmentioning
confidence: 94%
“…Jin et al (2011) reported an association between IL-17 gene polymorphisms and susceptibility to asthma in a Korean population, and suggested that the rs1889570 polymorphism was correlated with the development of asthma. Shen et al (2015) reported that the IL-17 rs2275913 and rs3819024 variant alleles were associated with a decreased risk of rheumatoid arthritis, while the IL-17 rs3819025 and rs8193036 variant alleles were correlated with an increased risk of rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Although the Th17 cytokines, IL-17A and IL-17F [26,27], and SNPs of IL-17A or IL-17F gene [28][29][30][31] have previously been shown Table 3 Associations of genotype with allergic rhinitis or allergic rhinitis plus asthma risk. to be associated with asthma, to our knowledge this is the first study to report a genetic association between IL-17A and IL-17F genes and allergic rhinitis.…”
Section: Discussionmentioning
confidence: 99%